Peran Perempuan dalam Meningkatkan Ekonomi Rumah Tangga Perspektif Maqashid Syariah Jasser Auda (Studi Kasus di Kecamatan Tengaran Kabupaten Semarang) - Nirmalasari, Shindita Apriliani; Putri, Nurchalisa (Program Studi Magister Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam, Universitas Islam Negeri Sunan Kalijaga, 2022)
This study discusses how the role of women from a domestic role to a public role to help improve the household economy in the perspective of Jasser Auda's maqashid sharia. The method used is descriptive-qualitative method with data sources derived from primary data through interviews of women working in the garment area of ​​Tengaran District. Women who work due to household economic needs, namely fulfilling daily life, including food, children's education costs, paying installments and other needs. Judging from the maqashid sharia, the role of women who work to improve the household economy is included in the context of achieving a prosperous life so that this is in accordance with the maqashid sharia concept, namely hifz al-nafs which is the protection of human rights, hifz al-nasl, namely protection of the family and hifz al-mal, namely maintaining wealth. The participation of women in the world of work not only has an impact on the economic welfare of the family but also contributes to changing the mindset and economic order of the region.